Avaliação da espectroscopia Raman intensificada por superfície em papel filtro e métodos quimiométricos na quantificação de fármacos - Sallum, Loriz Francisco (Universidade Federal de São Carlos, 2014)
Raman spectroscopy has been widely used for pharmaceutical analysis in recent decades due to advances of this technique, related to the development of electronics, optics and fundamental studies. As a consequence to the advantages of the technique of Raman signal enhancement and rapid data acquisition, SERS has become a useful analytical tool for quantifying active ingredients, detecting interferents, and assist in many other areas. In this work silver nanoparticles were synthesized by Tollens reagent using filter paper as the substrate, pre- treatment of the substrate influences its porosity, reactant concentrations, temperature and time of reaction being checked by fractional factorial design and central composite design, getting the synthesis with the highest enhancement factor in SERS signal. The analysis was performed with a Raman spectrometer with a laser wavelength of 785 nm and the nanoparticles were analyzed by Xray diffraction, energy dispersive spectroscopy and scanning electron microscopy. For the calibration models of nicotinamide and acetylsalicylic acid, it was chosen the most intense peak as reference. In summary, the present work investigated the detection and quantification of drugs in question using synthesized substrate. To this end, experimental design aimed at optimizing the synthesis of the substrate for possible quantification of active principles in presence of excipients in commercial products.
Evaluation of surface enhanced raman spectroscopy on paper filter substrate and chemometric methods in determination of drugs
Keywords: Quimiometria; Fármacos; Nanopartículas; Raman, Espectroscopia de; CIENCIAS EXATAS E DA TERRA::QUIMICA